2021
DOI: 10.3390/nu13113709
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards Olive Oil Usage, Domestic Storage, and Knowledge of Quality: A Consumers’ Survey in Greece

Abstract: Consumption of unbranded olive oil obtained in bulk has previously been reported to be very high in Greece, underlining the need to investigate knowledge regarding its health attributes and storage practices, two areas that can affect oil quality. This study aimed to investigate Greek consumers’ use and choice of olive oil, their knowledge about its quality, as well as domestic storage practices of olive oil. A cross-sectional survey was conducted in a representative sample of 857 Greek households that consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Although 74% of the 410 answers were affirmative to give economical support to this additional guarantee, 26% disagreed because they thought virgin olive oil was quite expensive already. This aspect would require a specific study since the price sensitivity of consumers depends on many social and economic factors, which also have geographical differences and evolve over time [ 10 , 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although 74% of the 410 answers were affirmative to give economical support to this additional guarantee, 26% disagreed because they thought virgin olive oil was quite expensive already. This aspect would require a specific study since the price sensitivity of consumers depends on many social and economic factors, which also have geographical differences and evolve over time [ 10 , 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted by Marakis et al in Greece revealed that a significant portion of participating households (60.3%) utilized olive oil produced by themselves, their extended family, or friends, while only 27.4% purchased branded olive oil. Moreover, approximately 57% reported using EVOO [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Virgin olive oil is also used in the management of catering and product supply processes which is not necessarily linked to its territorial origin and is easily available on the market at more accessible consumer prices than EVO oils or those with a protected designation of origin [23]. As a result, the market for EVOO that has been certified by brands of origin and organic production is dominated by household use [24,25] which has grown during the epidemic because of the restrictions that were put in place to stop the spread of the disease.…”
Section: Introductionmentioning
confidence: 99%